Uji Validitas Pengembangan Lembar Kerja Siswa (LKS) Biologi Berbasis Pendekatan Saintifik Pada Materi Perubahan Lingkungan dan Daur Ulang Limbah SMA Kelas X - Kholisotul Hidayah; Supiana Dian Nurtjahyani (Universitas Sebelas Maret, 2018)
Implementation of the learning process at SMAN 1 KEREK still uses conventional approach based learning. Learning methods such as lectures and question and answer still apply to the school. If this conventional approach-based learning is still applied in the modern era, it is feared that it will affect student's learning outcomes with 65% of the learning completeness score and KKM (70) which means that KKM has not reached the value of KKM. The currently used Student Worksheet is still simple in terms of materials, drawings and language used, so the need for the development of Student Worksheet (LKS) based on the Scientific Approach.In this environmental change and waste recycling materials LKS development uses Borg and Gall development methods. The purpose of this research is to find out the result of validity test of Student Worksheet based on scientific approach on environmental change and waste recycling materials and to improve student learning result SMAN 1 KEREK. The instrument used for this research is the questionnaire. Validity test results obtained from media experts with an average value of 83.1%, and from material experts obtained an average of 84% with criteria very valid and fit to be used as teaching aids, thus from the validity test results can be concluded that product development of Student Worksheet (LKS) based on biological approaches scientifically feasible to use and able to improve student learning outcomes SMAN 1 KEREK.